Comparison of financial and social performance in conventional and Islamic banking in Indonesia - Dini Hasanah; Ascarya Ascarya; Murniati Mukhlisin (Tazkia Islamic Finance and Business Review, 2026)
This study examines the comparison of financial and social efficiency between Islamic and conventional banks in Indonesia during the 2012–2020 period. Using a quantitative descriptive approach, the study applies Data Envelopment Analysis (DEA) with two models: the intermediation approach for financial efficiency and the production approach for social efficiency. The sample consists of 10 Islamic banks and 31 conventional banks selected from institutions consistently reporting CSR realization. The results indicate that Islamic banks demonstrate higher technical efficiency (TE) and pure technical efficiency (PTE) than conventional banks in both financial and social performance. However, financial efficiency values are consistently higher than social efficiency values for both banking types, indicating a stronger orientation toward financial performance. Scale efficiency (SE) in social performance shows conventional banks outperforming Islamic banks. The findings highlight the need for both banking systems to enhance social efficiency to achieve balanced two-dimensional efficiency aligned with sustainable finance principles.